Tailoring dual antiplatelet therapy for stroke prevention: a meta-analysis of timing, duration, regimen, and stroke subtypes - Alhawiti, Naif M.; Fouda, Sherouk; Alotaibi, Naser D.; Madkhali, Hassan A.; Alsharef, Fahad K.; Alhawiti, Jamal M.; El-Metwally, Ashraf (Frontiers in Pharmacology, 2025)
BackgroundDual antiplatelet therapy (DAPT) is commonly used for secondary stroke prevention, but the optimal timing and duration of treatment remain uncertain. This meta-analysis investigated the efficacy and safety of DAPT compared to any single antiplatelet therapy in stroke patients. We examined the effectiveness of DAPT versus monotherapy, stratified by stroke type, timing of intervention onset, and duration of DAPT.MethodsWe systematically searched electronic databases for randomized controlled trials (RCTs) comparing DAPT with any single antiplatelet therapy in stroke patients. Data from 30 RCTs involving 75,504 patients were pooled using a random-effects model. The key outcomes were recurrent ischemic stroke, major adverse cardiovascular events (MACE), and major bleeding. Additional studied outcomes included hemorrhagic stroke and mortality. Subgroup analysis examined the effectiveness of DAPT versus any single antiplatelet therapy, stratified by stroke type (ischemic stroke, lacunar stroke, and TIA or ischemic stroke), timing of intervention onset (within 12 h, 24 h, 48 h, 72 h, and 7–180 days), duration of DAPT (short-term: up to 30 days; long-term: beyond 30 days) and DAPT regimens (Aspirin and Clopidogrel, Aspirin and Cilostazol, Aspirin and Dipyridamole, and Clopidogrel and Cilostazol, etc.).ResultsDAPT significantly reduced recurrent ischemic stroke (RR 0.69, 95% CI 0.60–0.79) and MACE (RR 0.77, 95% CI 0.69–0.87), but did not significantly affect hemorrhagic stroke (RR 1.28, 95% CI 0.80–2.07), major bleeding (RR 1.10, 95% CI 0.91–1.33), or mortality (RR 1.01, 95% CI 0.88–1.15). Subgroup analyses showed that aspirin plus clopidogrel reduced recurrent stroke (RR 0.69, 95% CI 0.59–0.82) and MACE (RR 0.82, 95% CI 0.75–0.91). Early DAPT initiation (within 12–24 h) significantly reduced recurrent ischemic stroke (RR 0.73, 95% CI 0.57–0.92 and RR 0.66, 95% CI 0.52–0.84, respectively) and MACE (RR 0.78, 95% CI 0.62–0.98 and RR 0.81, 95% CI 0.72–0.93, respectively), but increased major bleeding (RR 2.32, 95% CI 1.10–4.86 and RR 1.34, 95% CI 1.20–1.49, respectively). Short-term DAPT (≤30 days) showed a greater reduction in recurrent ischemic events (RR 0.65, 95% CI 0.53–0.79) than long-term DAPT (>30 days; RR 0.72, 95% CI 0.60–0.86).ConclusionDAPT effectively reduces recurrent ischemic stroke and MACE, especially when initiated within 12–24 h using aspirin plus clopidogrel. Short-term DAPT (≤30 days) may be optimal for recurrent stroke prevention. Clinicians should carefully weigh benefits and risks when personalizing DAPT strategies.